Dynamic Relationship between Corruption and Youth Unemployment : Empirical Evidences from a System GMM Approach - Bouzid, Bechir N. (World Bank, Washington, DC, 2016)
This paper addresses the causal relationship between corruption and youth unemployment from two different perspectives. The discussion starts by asking how the corruption practices within government institutions that encourage the payment of bribes to access the job opportunities contribute to reducing the efficiency of the resources (labor force) allocations. The resources are diverted from the most productive economic sectors toward those (usually less efficient economic sectors) where self-motivated officials have more discretionary power in selecting the candidates who are less qualified for the job. The challenge is to examine how bribed bureaucrats are more concerned by their own personal interests at the expense of national welfare when positively reacting to the highest bribe payers. Second question addressed is why the resulting mismatching between supply and demand in the labor market tends to sustain its underlying causes (i.e., bribes) by giving more incentive to new agents and economic actors to adopt these practices. Using a system GMM approach that simultaneously account for the dynamic effect between perceived bribery among officials and the youth unemployment rates, the paper finds that, after controlling for various macroeconomic and institutional factors, the development of corruption practices tend to increase the unemployment rate among youth and educated job seekers which in turn contribute to sustain those unlawful practices by forcing the latter to bribe rent seeking government officials in order to secure a job.